Особливості захисту трудових прав працівників щодо яких здійснюється дисциплінарне провадження - Глушкова, Д. В.; Hlushkova, D. V. (Юридична наука. - 2019. - № 12 (102), т. 2. - С. 308-314, 2019)
Визначено, що захист трудових прав працівників, відносно яких розпочато дисциплінарне провадження, включає в себе чотири основні форми. Перші дві, - самозахист та діяльність профспілкових організацій, - є внутрішніми формами захисту трудових прав, які використовуються безпосередньо в процесі дисциплінарного провадження. Вони мають високий ступінь оперативності та гнучкості, адже реалізуються на будьякому етапі даної процедури. Інші дві форми, а саме звернення до комісій по трудових спорах та судовий захист, – передбачають здебільшого оскарження прийнятих в ході дисциплінарного провадження рішень, які порушують трудові права та інтереси працівника.

The relevance of the article lies in the fact that one of the most important aspects of carrying out disciplinary proceedings is ensuring and protecting the labor rights of employees for whom the specified procedure is carried out. The necessity of their disclosure is connected: firstly, with the high level of conflict of the disciplinary proceedings procedure, within the framework of which a person's guilt in an offense is proven, which can potentially cause subjective resistance; secondly, the possibility of a negative change in the employee's labor law status, or in general his loss of such status due to dismissal; thirdly, defining the protection of workers' rights as the main principle of disciplinary proceedings. The article, based on the analysis of scientific views of scientists and the norms of current legislation, reveals the general theoretical meaning of the concept of "legal protection". The author's definition of the category "legal protection of labor rights of employees subject to disciplinary proceedings" is proposed. The forms and methods of legal protection of labor rights of employees in respect of which disciplinary proceedings are carried out are singled out and characterized. It was concluded that the protection of the labor rights of employees against whom disciplinary proceedings have been initiated includes four main forms. The first two – self-defense and the activity of trade union organizations – are internal forms of protection of labor rights that are used directly in the process of disciplinary proceedings. They have a high degree of efficiency and flexibility, because they are implemented at any stage of this procedure. The other two forms, namely appeals to commissions for labor disputes and judicial protection, mostly involve appeals against decisions made during disciplinary proceedings that violate the labor rights and interests of the employee.

Определено, что защита трудовых прав работников, в отношении которых начато дисциплинарное производство, включает четыре основных формы. Первые две - самозащита и деятельность профсоюзных организаций - являются внутренними формами защиты трудовых прав, которые используются непосредственно в процессе дисциплинарного производства. Они обладают высокой степенью оперативности и гибкости, ведь реализуются на любом этапе данной процедуры. Другие две формы, а именно обращение в комиссии по трудовым спорам и судебную защиту, предусматривают в основном обжалование принятых в ходе дисциплинарного производства решений, нарушающих трудовые права и интересы работника.
Peculiarities of protection of labor rights of employees subject to disciplinary proceedings
Глушкова, Д. В. Особливості захисту трудових прав працівників щодо яких здійснюється дисциплінарне провадження / Глушкова Д. В. // Юридична наука. - 2019. - № 12 (102), т. 2. - С. 308-314.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; правовий захист; legal protection; правовая защита; трудові права; labor rights; трудовые права; дисциплінарне провадження; disciplinary proceedings; дисциплинарное производство; трудова дисципліна; labor discipline; трудовая дисциплина; працівник; employee; работник